Synthesis, properties, and prospective medical applications of metal-organic frameworks - Hyjek, Kornelia; Kuterasiński, Łukasz; Piskorz, Witold; Jodłowski, Przemysław J. (Chemical and Process Engineering, 2025)
Researchers strive to develop novel delivery systems for therapeutic substances and new therapies. The aim is to maximize the efficacy of conducted therapy while maintaining controlled drug delivery profiles and minimizing the side effects of therapy. Currently, numerous methods of drug administration are in use. Simultaneously, novel potential drug cargos, such as metal-organic frameworks, quantum dots, carbon nanotubes, or dendrimers, are under vigorous investigation. This paper aims to consider metal-organic frameworks (MOFs), which are composed of metal ions/clusters coordinated to organic linkers forming one-, two-, or three-dimensional materials with unprecedentedly large specific surface areas, high porosity, and a capability of a high degree of modifications. They have many potential applications, and due to their low toxicity, high biocompatibility, and bioavailability, they are considered materials of the “medicine of the future”. This review presents the state-of-the-art concerning the recent progress on the metal-organic frameworks, particularly on synthesis and characterization of MOFs, including their classification and possibilities of their modification. In the present paper, the recent state-of-the-art of biomedical applications, such as innovative cancer therapy, bone regeneration, bioimaging, biosensing, and upgrade delivery system based on MOFs is provided. Furthermore, MOF’s toxicity and forward-looking perspectives have been thoroughly discussed.